Materiales reciclados y las actitudes de protección del medio ambiente en los niños de la Institución Educativa Inicial Nº 728, Caballococha 2023 - Ruiz Carrera, Silfides Rocio (2024)
The objective of this study was to determine the relationship between the use of recycled materials and environmental protection attitudes in the children of the Initial Educational Institution Nº728, Caballococha 2023. The research approach is quantitative in nature, relational and the design is established as non-experimental, correlational and transectional. The total population (N) was 170 children belonging to the institution. A sample size equal to the population size was chosen due to practical considerations. Data collection was carried out through observation, using an observation guide as a tool that was previously validated by experts. The results derived from the analysis of the degree of association between the variables, the Spearman correlation coefficient, which stands at rs= 0.715, reveal a high relationship between the use of recycled materials and environmental awareness in children. Therefore, a forceful conclusion emerges: there is a significant connection between the relationship between the use of recycled materials and the attitudes of environmental protection in the children of the Initial Educational Institution Nº728, Caballococha 2023.